Reversing the gaze what if the other were you? - Makaping, Geneviève 1958- (Other voices of Italy, 2023)
Tired of being scrutinized, criticized, and fetishized for her black skin, Cameroon-born scholar Geneviève Makaping turns the tables on Italy's white majority, regarding them through the same unsparing gaze to which minorities have traditionally been subjected. As she candidly recounts her experiences-first across Africa and then as a migrant Black woman in Italy-Makaping describes acts of racist aggression that are wearying and degrading to encounter on a daily basis. She also offers her perspective on how various forms of inequality based on race, color, gender, and class feed off each other. Reversing the Gaze invites readers to confront the question of racism through the retelling of everyday occurrences that we might have experienced as victims, perpetrators, or witnesses